Pengaruh Audit Tenure, Reputasi Kantor Akuntan Publik (KAP), dan Latar Belakang Pendidikan terhadap Kualitas Audit Wilayah Batam - Agung Joni Saputra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This research was conducted to find out about quality of auditor located in Batam Island witch variables including Audit Tenure, Reputation of public accounting firm, amd educational background. Research Methodology: This study is qualitative research or by using a questionnaire where the target populations is auditors who working in public accounting firm in Batam Island. Result: The results of this study simultaneously show that auditor tenure, reputation of public accounting firm, and educational background have an effect on audit quality. While partially only audit tenure has an effect on audit quality, instead of reputation of public accounting firm and educational background have no effect on audit quality. Limitation: The numbers of variables selected in this study is limited, as well as the number of samples studied. Contribution: It is hoped that this research can be used as reference material for those who wish to do further research on this topic and is expected to be useful for company managers in an effort to maximize company value as their main objective.